Survey of Web Media Needs With Canva on PAI At The Senior High School Level - Norhidayah, Siti; Hady Ningsih, Salsabila; Yuliani, Hadma (Jurnal Amal Pendidikan, 2024)
This research is motivated by the need for Islamic Religious Education (PAI) learning media using technology. One of the media that can be utilized is web-based media. The purpose of this research is to analyze: 1) Students' and teachers' responses related to web-based PAI learning media, 2) Students' needs related to web-based learning media in accordance with student characteristics, and 3) The need for web-based learning media with Canva application. The method used was a mixed method with quantitative and qualitative approaches. Quantitative data were collected through questionnaires filled out by 66 students from 159 populations in this study. The results of this study showed that the majority of students responded positively to the use of web-based PAI learning media where 50% of students considered the media quite helpful and 46.97% of students considered web-based media very helpful.